Integração lavoura pecuária com uso de aveia preta e cornichão no inverno e milho em sucessão - Ducati, Camila (2014)
Were conducted for two years, with two studies to evaluate the use of oat long cycle Iapar 61 single or grown in association with legumes birdsfoot trefoil, with planting of corn in succession as a summer crop. The first study evaluated the structural, production characteristics, nutritional value of oat (Avena strigosa Iapar 61) grown single or associated with birdsfoot trefoil (Lotus corniculatus cv. St. Gabriel). The second experiment was conducted in two years with the aim to evaluate the structural , production characteristics , gas exchange IRGA (Infra Red Gas Analyser , Li - 6400XT , Licor , Lincoln , Nebraska) and chlorophyll content (SPAD index) of maize grown in succession to winter crops mentioned above . In the first experiment, two courts of oats in the first year and grazing periods in the second year, with average intervals of 30 days. The experimental design was a randomized complete block design with split plot, with the first year: two cropping systems: single or intercropped with birdsfoot trefoil with two periods of four replicates and oats oatmeal. In the second year, four tillage systems: conventional tillage oats, oat stubble tillage on corn, oats overseeded area of birdsfoot trefoil and single, with three cycles of growth and four replications. In the second study with corn, the experimental design used in the first and second year was a randomized split plot with blocks respectively. The following winter crops Corn was studied in succession: oat conventional tillage, no-till oats, oats in combination with birdsfoot trefoil, birdsfoot single, oats associated with nitrogen fertilization on ryegrass and oats associated with ryegrass nitrogen fertilization, with four replications. After planting corn the second year, we assessed the structural features for 70 days. Before the corn harvest, were picked manually ears of corn in three rows of four meters, which evaluated the number of grain rows, number of kernels per row, ear diameter, ear length, subsequent to these reviews, was made the threshing of grain for measurement of productivity data. The findings of the first study show that oats have reduced their production when combined with birdsfoot dry matter, but the total production (oat + birdsfoot trefoil) equates to the other treatments. In the first year dry matter yield of oats was higher when associated with birdsfoot the second cut (3750 kg ha - 1) compared to that obtained in the tillage of oat (2599 kg ha -1). In the second year, the highest dry matter production of oat occurred before the second grazing under no-tillage (4451.98 kg ha - 1). Oats elevates the apical meristem with the succession of grazing or cutting. The oat presents before the first grazing, high nutritional value, with high average levels of protein (22.25 %) for all treatments. However, at the end of its cycle the association of birdsfoot trefoil with oats, helped to raise the crude protein content of forage as this is in the final stage of its cycle. In vitro digestibility of DM was high for both oat grown under conventional tillage (73.04 %) and direct (77.05 %), and for birdsfoot trefoil (78.37 %), but decreased at the end of the cycle oat. There was no benefit to the cultivation of corn grown after legume and should performed new tests assessing possible causes, including allelopathic effect and competition among plants